Rehabilitation following high tibial osteotomy - Aalderink, K. J.; Shaffer, M.; Amendola, A. (Clinics in Sports Medicine, 2010)
Tibial osteotomy is an effective surgical intervention for treating knee malalignment associated with pain or arthrosis in young and active patients. Although the techniques have evolved, the basic principle has been used for many years. The advent of improved fixation devices has allowed for earlier and more aggressive return to activity, resulting in the need for new rehabilitation guidelines that are individualized to patient pathology, expectations, and abilities.